Politicians' Payments in a Proportional Party System - Heléne Berg (Center for Economic Studies and ifo Institute (CESifo), 2018)
Is politics a lucrative business? The question is approached in this paper, as one of few to quantify the monetary returns to holding political office in a typical developed democracy where parties are the main political actors. By applying a difference-in-difference setting with a carefully chosen control group to rich data on candidates to the Swedish national parliament, both short and long-run effects of being elected on different types of income are estimated. Results show that, yes, mostly thanks to relatively high remuneration while still in office, politics can be a lucrative business. In the long-run however, the effect is instead compositional in the sense that ex-politicians receive more pension income and work less.
Keywords: C23; D72; J44; 330; returns to politics; difference-in-difference